Monitoring the impact of the economic crisis on informatization strategies of Polish companies and institutions in the years 2009-2011 - Dyczkowski, Mirosław; Dyczkowski, Tomasz (Monitorowanie wpływu kryzysu gospodarczego na strategie informatyzacyjne polskich przedsiębiorstw i instytucji w latach 2009–2011, 2012)
The paper discusses the outcome of a comparative research project from 2009– 2011 which aimed at determining how the recent economic crisis influenced informatization strategies in Polish companies and institutions. The obtained results validated a working hypothesis that the economic crisis did affect – to a smaller or greater extent – short- and long-term informatization strategies in the majority of companies or institutions. Despite the fact that the relative importance of the identified strategy modification, the intensity of their visible symptoms or areas of IT applications where they were most noticeable differed from year to year, those variations were minor and concerned some elements of informatization strategies and of IT applications only. Details are included in this paper
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 23-37
Keywords: economic crisis; comparative surveys; changes of informatization strategies; kryzys gospodarczy; ankietowe badania porównawcze; zmiany strategii informatyzacji